Reflecting reality: pager simulations in undergraduate education. (October 2014) - Dickinson, Mike; Pimblett, Mark; Hanson, Jacky; Davis, Mike
Summary Background Fifth‐year medical students build on their experiences of simulation and clinical placement to undertake a period of pager contact, during which they must respond appropriately to a variety of 'bleep' messages, culminating in the team management of a complex scenario. Context In anticipation of their graduation to foundation‐year doctors, fifth‐year students in their final term on clinical placement at Lancashire Teaching Hospitals experience a period of time on call, when they receive a series of pager messages that they must manage whilst on clinical placement. They are expected to manage the variety of random events as if they were doctors on call. Innovation With the agreement of all affected parties, students experience some simulated events of the type that they may experience while on call as foundation‐year doctors. They are required to respond appropriately to these and are offered feedback on performance after they gather for a cardiac arrest simulation. Discussion This has been a very popular and impactful experience for final‐term undergraduates as they anticipate the challenges of becoming foundation‐year doctors. The need for effective management of clinical and non‐technical skills presented in an ill‐defined problem space is an appropriate challenge that serves to reassure them about their capacity to manage the unexpected. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> [The students] are expected to manage the variety of random events as if they were doctors on call </boxed-text>